PDE10A as a novel diagnostic and therapeutic target in cancer: insights and challenges - Ghoflchi, Sahar; Nakhaei, Ali; Abbasinezhad-Moud, Farzaneh; Jalili-Nik, Mohammad; Cimino, Patrick J. (Frontiers in Oncology, 2025)
Phosphodiesterase 10A (PDE10A) is a dual-substrate enzyme that hydrolyzes both cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (cGMP), playing a critical role in regulating intracellular signaling pathways. While its function has been extensively studied in the central nervous system, emerging evidence highlights its broader physiological and pathological relevance, including its involvement in cancer. Functionally, it modulates key signaling pathways such as cAMP/protein kinase A (PKA) and cGMP/protein kinase G (PKG), influencing cell proliferation, differentiation, and apoptosis. In cancer, PDE10A exhibits a context-dependent role. It functions as an oncogene in cancers such as colorectal, ovarian, gastric, and non-small cell lung cancers through overexpression and downstream activation of the Wnt/β-catenin, MAPK/ERK, and PI3K/AKT pathways. Pharmacological inhibition of PDE10A using selective inhibitors has demonstrated potent anti-tumor effects in preclinical models by restoring cyclic nucleotide levels and suppressing oncogenic signaling. Conversely, in glioblastoma (GBM), PDE10A acts as a tumor suppressor, and its knockdown promotes tumor progression via activation of the PI3K/AKT pathway. These findings showed the ability of PDE10A to be considered as a promising biomarker and therapeutic target in oncology; however, it is suggested to examine the tissue-specific expression of PDE10A, baseline cyclic nucleotide levels, cross-talk with other pathways, differences in the degree and duration of PDE10A suppression, and the interplay between PDE10A-mediated cyclic nucleotide signaling and compensatory oncogenic pathways for an effective therapy as observed in other PDEs family reviewed in this manuscript.